Ecoindicators: An R Package for the Identification of Indicator Taxonomic Units - Andrés Esteban Duhour; Hernán de la Vega; Liliana Falco; Carlos Coviella; Nicolás Velazco; Rosana Sandler; Macarena Rionda; Mónica Díaz Porres; Leonardo Saravia (Journal of Open Research Software, 2023)
The sensitivity of some taxonomic groups to environmental conditions allows for their use as ecological state indicators. In ecological communities, this analysis is of interest to know which species or taxa are indicators of particular environment conditions, taking into account their presence in a set of sampling units. There are different approaches to estimate indicator species, in this work we develop a new tool for this task identifying indicator units defined as species (or taxa) whose observed frequencies are not uniform between environments or groups of sample units. The package provides methods to estimate the indicator species, the belonging of new samples to a given environment, and returns the frequency of taxonomic units in a selected combination of environmental factors as an estimation of the ecological niche. EcoIndicators was tested on a data set provided with the package and on independent samples of soil fauna communities and is freely available in https://github.com/lsaravia/EcoIndicators.